PEMENUHAN HAK PEKERJA PEREMPUAN DI BENCOOLEN MALL KOTA BENGKULU DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Frabio, M. Rulian (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2022)
Abstract: The formulation of the problem in this study which includes how to fulfill the rights of women workers in Bencoolen Mall in the perspective of positive law and Islamic law? The type of research used is field research (Field Research). Data collection techniques were carried out through observation, interviews and documentation. This study concludes that 1). The implementation of the fulfillment of the rights of women workers at Bencoolen Mall in the perspective of positive law and Islamic law has been fulfilled and implemented optimally. 2). Fulfillment of the rights of women workers is regulated in 15 (fifteen) laws and regulations, essentially there are eight rights of women workers guaranteed by the government given by Bencoolen Mall to its female workers. The rights that must be obtained by female workers consist of: the right to rest for menstruation, the right to get protection during pregnancy and the prohibition of layoffs for workers who are married, pregnant, and giving birth, the right to rest during pregnancy, abortion and childbirth, and the opportunity to breastfeed. Furthermore, the obligations that must be carried out by the company in fulfilling the rights of women workers consist of: the obligation to provide breastfeeding facilities, the obligation not to discriminate and employ women workers at night and the obligation to guarantee protection from violence and harassment. 3). In the study of Islamic law, it shows that the rights of women workers are very much considered, especially in aspects related to the fulfillment of the rights to the income earned from the work. The right to get an appropriate wage (sura An-Nissa: 32, An-Nisa: 124), the right to leave and work relief (sura Al-Baqarah: 286) and the right to get comfort and protection (At-Taubah: 71 and An-Nissa: 34). Keywords: Women Workers Rights, Islamic Law, Positive Law. Abstrak: Rumusan masalah dalam penelitian ini yang meliputi bagaimana pemenuhan hak pekerja perempuan di Bencoolen Mall dalam perspektif hukum positif dan hukum Islam? Jenis penelitian yang digunakan ialah penelitian lapangan (Field Research). Teknik pengumpulan data dilakukan melalui Observasi, wawancara dan Dokumentasi. Penelitian ini menyimpulkan bahwa 1). Pelaksanaan pemenuhan hak pekerja perempuan di bencoolen mall dalam perspektif hukum positif dan hukum Islam sudah terpenuhi dan terlaksana dengan maksimal. 2). Pemenuhan hak-hak pekerja perempuan tersebut diatur di dalam 15 (Lima belas) peraturan perundang-undangan yang intinya terdapat delapan hak pekerja perempuan yang dijamin oleh pemerintah yang diberikan oleh bencoolen mallkepada pekerja perempuannya. Hak yang wajib didapat oleh pekerja Perempuan terdiri dari: Hak Istirahat haid, Hak mendapatkan Perlindungan saat hamil dan larangan PHK bagi pekerja yang menikah, hamil, dan melahirkan, Hak Istirahat Hamil, Gugur Kandungan dan Melahirkan, dan Kesempatan menyusui. Selanjutnya Kewajiban yang harus dilaksanakan oleh perusahaan dalam memenuhi hak pekerja perempuan yang terdiri dari: kewajiban menyediakan fasilitas menyusui, kewajiban untuk tidak melakukan deskriminasi dan mempekerjakan pekerja perempuan di malam hari dan kewajiban untuk memberikan jaminan perlindungan dari kekerasan dan pelecehan. 3). Dalam kajian hukum Islam menunjukan bahwa hak pekerja perempuan sangat diperhatikan terutama dalam aspek-aspek yang berkaitan dengan segi hak pemenuhan atas pendapatan yang diperoleh atas pekerjaan tersebut. Hak mendapatkan upah yang sesuai (surah AnNissa: 32, An-Nisa: 124), hak cuti dan keringanan pekerjaan (surah Al-Baqarah: 286) dan hak mendapatkan kenyamanan dan perlindungan (At-Taubah: 71 dan An-Nissa: 34). Kata Kunci: Hak Pekerja Perempuan, Hukum Islam, Hukum Positif